2-phenyl-4-substituted quinazolines with activity against Bovine Viral Diarrhea Virus (BVDV): Biological evaluation and physicochemical properties - Fernandez, Gabriela Araceli (2019)
Bovine viral diarrhea virus (BVDV) belongs to the Pestivirus genus of the family Flaviviridae. Because BVDV infections lead to considerable financial losses within the livestock production, having effective and selective antivirals could be very useful. Viral RNA-dependent RNA polymerase (NS5B RdRp) is responsible for viral RNA synthesis. In previous studies, after in silico molecular screening with BVDV RdRp and in vitro evaluation, we identified molecules with anti-BVDV activity. Between them, N-(2-morpholinoethyl)-2-phenylquinazolin-4-amine (1) presented an EC50 value of 9.68±0.49 µM, and it was chosen for further optimization. Therefore, we synthesized 26 derivates of 1 via nucleophilic aromatic substitution (SNAr) reactions with several amines and anilines. Six derivatives showed improved antiviral activity (EC50 from 1.37±0.27 to 1.78±0.37 µM) with better selectivity index (SI) than 1. Derivative 1.9 with the highest SI (17.95) was further studied.Physicochemical properties of 1.9. The solubility of compound 1.9 was tested at 1.2, 6.8, and 7.4 pH values, employing the shake-flask method. As result, 1.9 presented good solubility values within the range generally observed for oral drugs: simulated gastric fluid (SGF, pH 1.2): 1060.8±100.2 µg/mL; simulated intestinal fluid (SIF, pH 6.8): 420.4±23.7 µg/mL; and phosphate buffered saline (PBS, pH 7.4): 187.2±5.0 µg/mL.Stability studies in different media and the encapsulation of the compounds are currently ongoing in our lab. We hypothesize that encapsulation could improve compound?s solubility. We will also test the cytotoxicity of these encapsulated compounds with the aim of obtaining better SI, which can be traduced in more promising candidates as anti-BVDV agents.In summary, we obtained potent anti-BVDV molecules after lead optimization. Biological characterization and in silico studies indicated that these compounds may act as BVDV-RdRp inhibitors.